Large-Scale User Facility Imaging and Scattering Techniques to Facilitate Basic Medical Research - Miller, Stephen D.; Bilheux, Jean-Christophe; Gleason, Shaun S.; Nichols, Trent L.; Bingham, Philip R.; Green, Mark L. (IntechOpen, 2011)
None